Distinguishing interpersonal and ideological prosociality:Introducing the construct of ideological prosociality. (April 2022) - Nezlek, John B.
Abstract: Prosociality refers to dispositions and behaviors intended to benefit others, and the present study assumed that these dispositions reflect people's values. Much of the research on prosociality has examined prosociality in what can be called the interpersonal domain, e.g., helping others. I propose that prosociality also exists in the ideological domain. People hold prosocial values that concern collectives, not specific individuals. Multilevel analyses of data collected in Wave 8 of the European Social Survey (44, 000 respondents in 23 countries) found positive relationships between ideological prosocial values and attitudes toward immigrants, refugees, and gays and lesbians, attitudes about the environment and climate change, social benefits, and income equality. Moreover, these relationships remained significant after controlling for participants' sex, age, income, education, political orientation, and happiness. In contrast, relationships between these attitudes and interpersonal prosocial values were either negative or not significant. Highlights: The construct of ideological prosociality is introduced. Ideological prosociality differs from interpersonal prosociality. Data from the European Social Survey (Wave 8, 2016) were analyzed. Ideological prosociality was positively related to ideological prosocial values and beliefs. Interpersonal prosociality was not related to ideological prosocial values and beliefs.